A call to action: informing research and practice in suicide prevention among individuals with psychosis - Chalker, Samantha A.; Sicotte, Roxanne; Bornheimer, Lindsay A.; Parrish, Emma M.; Wastler, Heather; Ehret, Blaire; DeVylder, Jordan; Depp, Colin A. (Frontiers in Psychiatry, 2024)
Although it is well established that individuals living with psychosis are at increased risk for suicidal ideation, attempts, and death by suicide, several gaps in the literature need to be addressed to advance research and improve clinical practice. This Call-to-Action highlights three major gaps in our understanding of the intersection of psychosis and suicide as determined by expert consensus. The three gaps include research methods, suicide risk screening and assessment tools used with persons with psychosis, and psychosocial interventions and therapies. Specific action steps to address these gaps are outlined to inform research and practice, and thus, improve care and prognoses among persons with psychosis at risk for suicide.